Cell‐Mediated Cytotoxicity in Lyme Arthritis. Issue 5 (20th March 2023) - Ordóñez, David; Lochhead, Robert B.; Strle, Klemen; Pianta, Annalisa; Arvikar, Sheila; Van Rhijn, Ildiko; Stemmer‐Rachamimov, Anat; Steere, Allen C.
Abstract : Objective: Obliterative microvascular lesions are found in the synovial tissue of ~50% of patients with post‐antibiotic Lyme arthritis (LA) and correlate with autoantibodies to certain vascular antigens. In this study, we identified lymphocytes with cytotoxic potential that may also mediate this feature of synovial pathology. Methods: The cytotoxic potential of lymphocytes and their T cell receptor (TCR) Vβ gene usage were determined using samples of peripheral blood mononuclear cells (PBMCs) and synovial fluid mononuclear cells (SFMCs) from patients with antibiotic‐responsive or post‐antibiotic LA. Cell phenotypes were analyzed using flow cytometry and intracellular cytokine staining. Immunohistochemistry was performed on post‐antibiotic synovial tissue samples. Results: In SFMC and PBMC samples, the percentages of CD8+ T cells and double‐negative T cells (primarily γδ T cells) were greater among 22 patients with post‐antibiotic LA than in 14 patients with antibiotic‐responsive LA. Moreover, CD8+ T cells and γδ T cells often expressed cytotoxic mediators, granzyme A/granzyme B, and perforin. The same 3 TCR Vβ segments were over‐represented in both CD4+ T cells and CD8+ T cells in SFMC samples from post‐antibiotic LA patients. In synovial tissue samples from 3 patients with post‐antibiotic LA, CD8+ T cells intermixed with CD4+ T cells were seen around blood vessels, and 2 patients with microvascular damage had autoantibodies to vascular‐associated antigens. One of these 2 patients, the one in whom cytotoxicity appeared to be active, had complement (C5b–9) deposition on obliterated vessels. Very few natural killer cells or γδ T cells were seen. Conclusion: We propose that CD8+ T cell–mediated cytotoxicity, CD4+ T cell help, autoantibodies to vascular antigens, and complement deposition may each have a role in microvasculature damage in post‐antibiotic LA.